2016
DOI: 10.19045/bspab.2016.50093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertilizer priming on seed germination behavior and vigor of maize

Abstract: Laboratory experiments were conducted to examine the efficacy of fertilizer priming on seed germination behavior and vigor of two maize cultivars "Azam and Phari" at Agronomy Research Laboratory, University of Agriculture, Peshawar-Pakistan during 2015. Studied treatments include hydropriming (distilled water) and osmopriming with Calcium Ammonium Nitrate (CAN) at 0.5% for 24 hours. Non primed seed were used as control. Data were recorded on germination and vigor parameters according to standard procedures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
2
11
1
Order By: Relevance
“…Rapid and uniform field emergence are two vital rudiments to increase yield, quality and ultimately profits in crops. Uniformity and percentage of seedling emergence of direct-planted crops have a major impact on final yield and quality (Khan et al, 2016). Slow emergence results in smaller plants and weak seedlings, which are more vulnerable to soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid and uniform field emergence are two vital rudiments to increase yield, quality and ultimately profits in crops. Uniformity and percentage of seedling emergence of direct-planted crops have a major impact on final yield and quality (Khan et al, 2016). Slow emergence results in smaller plants and weak seedlings, which are more vulnerable to soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mature seeds tend to show a better germination performance at stress temperatures than those of earlier and later harvests, while advancement obtained by priming was greater in earlier harvests (Khan et al, 2016). Several studies on seed germination and emergence revealed the beneficial effects of seed priming by several ways (heat, smoke, soaking, leaching, temperature, scarification and NaCl salinity) (Ahmed et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They have reported that Canola cultivars positively responded in optimum temperature range to sulphur fertilization in term of seed yield and oil quality. (Barnola et al (1987), Samreen, et al (2016), Anwar et al (2016), Khan et al (2016) and Imran et al (2016) [2,10,11,12,20] concluded that Oscar cultivar increased seed yield 53% as compared to control plots when there were no fluctuation in temperature. Sulphur at the rate of 45 kg ha -1 increased seed yield, biological yield, and quality of rapeseed.…”
Section: Response Of Germination To Changed Climatementioning
confidence: 99%
“…The global warming caused by climate change is likely to affect crops throughout the life cycle due to increased temperature, moisture stress, heat waves, the possible emergence of new major insect-pests and disease [2,[11][12][13][14]. It has been reported that mungbean has high nutritive value, and due to this, has advantage over the other pulses known as king of the pulse crop.…”
Section: How Climate Change Is a Threat And Challenge For Food Securitymentioning
confidence: 99%
“…The regional climates have great importance in respect of agricultural productivity, food security, and livelihood. Recent studies have showed that plants and crop responded positively to reginal climate and showed ameliorating effect in term of grain yield, plant height, thousand grain weight, dry matter portioning, biological yield, oil yield, and quality of the crops [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%